HCMV carriage in the elderly diminishes anti-viral functionality of the adaptive immune response resulting in virus replication at peripheral sites - Davies, Emma L.; Noor, Mahlaqua; Lim, Eleanor Y.; Houldcroft, Charlotte J.; Okecha, Georgina; Atkinson, Claire; Reeves, Matthew B.; Jackson, Sarah E.; Wills, Mark R. (Frontiers in Immunology, 2022)
Human cytomegalovirus (HCMV) infection and periodic reactivation is, generally, well controlled by adaptative immune responses in the healthy. In older people, overt HCMV disease is rarely seen despite the association of HCMV with increased risk of mortality; evidence from studies of unwell aged populations suggest that HCMV seropositivity is an important co-morbidity factor. HCMV genomes have been detected in urine from older donors, suggesting that the immune response prevents systemic disease but possibly immunomodulation due to lifelong viral carriage may alter its efficacy at peripheral tissue sites. Previously we have demonstrated that there were no age-related expansions of T cell responses to HCMV or increase in latent viral carriage with age and these T cells produced anti-viral cytokines and viremia was very rarely detected. To investigate the efficacy of anti-HCMV responses with increasing age, we used an in vitro Viral Dissemination Assay (VDA) using autologous dermal fibroblasts to determine the anti-viral effector capacity of total PBMC, as well as important subsets (T cells, NK cells). In parallel we assessed components of the humoral response (antibody neutralization) and combined this with qPCR detection of HCMV in blood, saliva and urine in a cohort of young and old donors. Consistent with previous studies, we again show HCMV specific cIL-10, IFNγ and TNFα T cell responses to peptides did not show an age-related defect. However, assessment of direct anti-viral cellular and antibody-mediated adaptive immune responses using the VDA shows that older donors are significantly less able to control viral dissemination in an in vitro assay compared to young donors. Corroborating this observation, we detected viral genomes in saliva samples only from older donors, these donors had a defect in cellular control of viral spread in our in vitro assay. Phenotyping of fibroblasts used in this study shows expression of a number of checkpoint inhibitor ligands which may contribute to the defects observed. The potential to therapeutically intervene in checkpoint inhibitor pathways to prevent HCMV reactivation in the unwell aged is an exciting avenue to explore.